Attosecond tracing of correlated electron-emission in non-sequential double ionization - Bergues, Boris; Kübel, Matthias; Johnson, Nora G.; Fischer, Bettina; Camus, Nicolas; Betsch, Kelsie J.; Herrwerth, Oliver; Senftleben, Arne; Sayler, A. Max; Rathje, Tim; Pfeifer, Thomas; Ben-Itzhak, Itzik; et al. (My University, 2012)
Despite their broad implications for phenomena such as molecular bonding or chemical reactions, our knowledge of multi-electron dynamics is limited and their theoretical modelling remains a most difficult task. From the experimental side, it is highly desirable to study the dynamical evolution and interaction of the electrons over the relevant timescales, which extend into the attosecond regime. Here we use near-single-cycle laser pulses with well-defined electric field evolution to confine the double ionization of argon atoms to a single laser cycle. The measured two-electron momentum spectra, which substantially differ from spectra recorded in all previous experiments using longer pulses, allow us to trace the correlated emission of the two electrons on sub-femtosecond timescales. The experimental results, which are discussed in terms of a semiclassical model, provide strong constraints for the development of theories and lead us to revise common assumptions about the mechanism that governs double ionization.